The Influence of Audiovisual Media on the IPAS Learning Outcomes of Fifth-Grade Elementary School Students - Deana Pinkan; Ika Yatri (Journal of Educational Sciences, 2026)
Elementary school students often experience difficulty understanding food chain concepts because interactions among organisms and energy transfer cannot always be observed directly. This condition highlights the need for learning media that can present abstract concepts in a more concrete and engaging way. This study aimed to examine the learning outcomes of fifth-grade students in Ilmu Pengetahuan Alam dan Sosial (IPAS) through the use of audiovisual media. The study employed a quantitative approach with a quasi-experimental design using a nonequivalent posttest-only control group. The sample consisted of 56 fifth-grade students from two parallel classes at SDN Susukan 07 Pagi, Jakarta, with 28 students in the experimental group and 28 in the control group. The experimental group received instruction using audiovisual media, whereas the control group received conventional instruction. Data were collected using 25 valid multiple-choice questions and analyzed using descriptive statistics, the Shapiro–Wilk test, Levene’s test, and an independent samples t-test. The results showed that the experimental group achieved significantly higher learning outcomes than the control group, with a p-value of 0.007 and a Cohen’s d of 0.75. The novelty of this study lies in examining audiovisual media as the primary instructional intervention in regular IPAS classroom learning, specifically for food chain concepts, without integrating it with a particular instructional model. This provides more direct evidence of the contribution of audiovisual media to improving elementary students’ learning outcomes.